2014
DOI: 10.1155/2014/639160
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Choroidal Thickness and Volume Measurements with Axial Length and Age Using Swept Source Optical Coherence Tomography and Optical Low-Coherence Reflectometry

Abstract: Purpose. To report choroidal thickness and volume in healthy eyes using swept source optical coherence tomography (SS-OCT). Methods. A prospective observational study of 122 patients examined with swept source OCT (DRI-OCT, Topcon, Japan). In each eye, we performed 256 horizontal scans, 12 mm in length and centered on the fovea. We calculated choroidal thickness manually with a built-in caliper and automatically using DRI-OCT mapping software. Choroidal volume was also automatically calculated. We measured axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 16 publications
2
41
0
Order By: Relevance
“…axial length have reported an inverse correlation between the two (12,14). Similar studies carried out on children have also revealed an inverse correlation between ChT and axial length (15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Original Research Articlementioning
confidence: 53%
See 1 more Smart Citation
“…axial length have reported an inverse correlation between the two (12,14). Similar studies carried out on children have also revealed an inverse correlation between ChT and axial length (15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Original Research Articlementioning
confidence: 53%
“…Studies on adults have shown that ChT decreases with age (11)(12)(13), and authors evaluating ChT according to noninvasive prospective observational study was granted by the local ethics committee.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in adults, differences have been shown between sexes in the foveal avascular zone (FAZ) surface area [7-9]. Similarly, no reference parameters exist for structural OCT in children, although the norms are likely to be different from adults due to the known differences in choroidal thickness with age [10-12]. The aim of the present study was to determine whether gender differences exist in the retinal microvasculature of children with and without vascular pathology using structural OCT and OCTA.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, although our understanding of choroidal characteristics has increased substantially in recent years, only a few reports to date have provided values for choroidal thickness in children. [7][8][9] In a recent study, age and axial length (AL) were determined to be negatively correlated with choroidal thickness and volume in adults. 7 Similarly, in a previous study, we also demonstrated a decrease in choroidal thickness with increasing myopia, age, and AL in adults.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In a recent study, age and axial length (AL) were determined to be negatively correlated with choroidal thickness and volume in adults. 7 Similarly, in a previous study, we also demonstrated a decrease in choroidal thickness with increasing myopia, age, and AL in adults. 8 However, although our understanding of choroidal characteristics has increased substantially in recent years, only a few reports to date have provided values for choroidal thickness in children.…”
Section: Introductionmentioning
confidence: 99%